Client issues in counselling and psychotherapy - Tolan, Janet , 1954-; Wilkins, Paul , 1946- (SAGE, 2012)
"This is the first humanistic counseling book to bring together commonly occurring client issues, exploring the origin and meaning of the difficulty, the therapeutic approach and process, and the outcomes. Extensive case material guides you through the nuances and potential pitfalls towards effective practice with clients. Drawing from a combined 50 years of experience in the field, Paul Wilkins and Janet Tolan bring together leading person-centered therapists to address how and why each problem can be eased by means of working with the person. This book should be on the desk of every counseling trainee, and is recommended reading for other practitioners of health and social care working with these client groups."